Experimental and numerical characterization of displacement field on biological tissues - Ribeiro, J.E. (2011)
"The need to understand the behavior of biological tissues, especially human tissue, has stimulated the development of experimental and" "numerical techniques that allow the characterization of such materials. Nowadays the use of experimental tests has been frequently replaced by the numerical simulation using finite element method, with important advantages from the standpoint of saving financial costs and time consumption." "The Digital Image Correlation (DIC) is a measurement technique which uses a mathematical correlation method to calculate the displacement on the plane surfaces of components or structures subjected to thermal or mechanical charges In this work were done two different experimental tests using the DIC to characterize hard and soft materials behavior and the respectively numerical comparison with a commercial finite elements" "code, Ansys®."